Barraquand Pinot et al. JAE Overcompensation and phase effects in a cyclic vole 2014 - Barraquand, Frédéric; Pinot, Adrien; Yoccoz, Nigel G.; Bretagnolle, Vincent (Dryad Digital Repository, 2014)
Vole abundance data and computer codes, in both R and Matlab, to reproduce the results presented in the main text and SI.